2019
DOI: 10.1111/dom.13701
|View full text |Cite
|
Sign up to set email alerts
|

The extent to which statins have improved cardiovascular outcomes: Lessons from randomized trials and observational studies of “real world” practice in people with diabetes

Abstract: Statins are the mainstay of therapy for cardiovascular risk reduction in patients with diabetes mellitus. It is estimated that there are more than half a billion patients with diabetes mellitus worldwide and the numbers of prevalent cases of diabetes are expected to increase in both developed and developing countries in the next decade. Statins reduce risk of mortality and morbidity mainly by reducing blood low density cholesterol. Statins, along with other medical treatments, are responsible for about half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
6
0
1
Order By: Relevance
“…A healthy lifestyle decreases significantly the risk of atherosclerosis. The treatment with statins reduces the risk both of myocardial infarction and stroke [9,10]. People who may benefit from preventive therapy should have a life expectancy of at least five years.…”
Section: Primary Preventionmentioning
confidence: 99%
“…A healthy lifestyle decreases significantly the risk of atherosclerosis. The treatment with statins reduces the risk both of myocardial infarction and stroke [9,10]. People who may benefit from preventive therapy should have a life expectancy of at least five years.…”
Section: Primary Preventionmentioning
confidence: 99%
“…27 Canadian guidelines recommend statins for all patients with established ASCVD, additionally, ezetimibe and PCSK9 inhibitors are recommended to lower LDL-C, 28 and decrease the risk of subsequent CV events in ASCVD patients above the LDL-C threshold of 1.8 mmol/L. 18,[29][30][31] However, despite an emphasis on secondary prevention of CV events with lipidlowering therapies, there remains a high residual risk for recurrent MACE outcomes and a substantial overall ASCVD burden. 19 Our study found that only 47.5% of patients with ASCVD and 69.3% of patients with an AMI event received statin therapy within 6 months after their events.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are usually prescribed especially in T2D patients to protect against cardiovascular complications [165]. The role of statins in COVID-19 is not clearly established, however, some observation should be done.…”
Section: Concomitant Medicationsmentioning
confidence: 99%